Robust mobile robot navigation using fuzzy type 2 with wheel slip dynamic modeling and parameters uncertainties. (1st November 2020) - Saidi, Yasmine; Nemra, Abdelkarim; Tadjine, Mohamed
ABSTRACT: In this paper, a full dynamic model for mobile robot with wheel slip is developed for robust navigation. The type 2 fuzzy logic controller algorithm is implemented and compared to the type 1 fuzzy controller using a differential drive wheels mobile robot (DDWMR) in the presence of wheel slipping from the perspective of control design. We present a dynamic model that explicitly relates perturbations to the vehicle slipping and parameters uncertainties. Both controllers are validated on different behaviors of navigation to evaluate their performances. Furthermore, many advanced robustness tests (modeling errors, localization uncertainties, loss of efficiency of motors, sliding ground) are established to compare the efficiency of each controller. Type 1 and interval type 2 fuzzy logic controllers are validated using V-REP robotic simulator on MATLAB® environment and real scenario are considered. The obtained results show clearly the performances of the IT2FLC comparing to the T1FLC controller especially when significant wheel slip and parameters uncertainty are considered.